PhoneMe Poetry: Mapping Community in the Digital Age - Balyasnikova, Natalia; James, Kedrick (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
In this paper we explore how place-based poetry mediated online enabled community self-representation. Located in the urban core of a large cosmopolitan Canadian city, the PhoneMe project brought together academic researchers and community members into a collaborative educational creative space. Community members created poems about specific places within their neighbourhood, dialed a designated phone number, and recorded the poem by leaving a voice message. Upon receiving the message, the academic team geotagged it on an interactive map, uploaded the poem’s text, featured a Google Streetview image of the location, and shared the post via social media. As the result, a new vision for this distinctive physical space emerged and reached the wider audiences via engagement with the poetic digital media. Plans have included include collaboration with urban libraries, the development of a new app, and have encouraged the use of engaged research-creation as a research method.